2002
DOI: 10.1007/s11661-002-0314-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the atmosphere on the sintering of aluminum

Abstract: 0.15Mg, and Al-12Sn made using air atomized aluminum powder and pressed to green densities of 75 to 98 pct were sintered under argon or nitrogen. Sintering in argon is only effective at high green densities when magnesium is present. In contrast, highly porous aluminum can be sintered in nitrogen without the need for magnesium. The oxygen concentration in the gas is reduced by the aluminum through a self-gettering process. The outer layers of the porous powder compact serve as a getter for the inner layers suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 29 publications
4
75
0
8
Order By: Relevance
“…6). The formation of aluminium nitride is an exothermic reaction which may occur if nitrogen gains a direct contact with the freshly exposed aluminium surface according to reaction (2) [11]:…”
Section: Microstructural Investigationsmentioning
confidence: 99%
“…6). The formation of aluminium nitride is an exothermic reaction which may occur if nitrogen gains a direct contact with the freshly exposed aluminium surface according to reaction (2) [11]:…”
Section: Microstructural Investigationsmentioning
confidence: 99%
“…Schaffer & Hall, 2002, suggested that the oxygen concentration in the nitrogen atmosphere is reduced by the aluminium through a self-gettering mechanism. The outer layers of the porous powder compact serve as a getter for the inner layers such that the oxygen partial pressure is reduced deep within the pore network.…”
Section: Fig 10 Oxide Layer Covering Aluminium Particlesmentioning
confidence: 99%
“…Para o caso do tratamento do alumínio, a atmosfera pode afetar significativamente suas propriedades finais e na obtenção de boa precisão dimensional (3) . Quando a atmosfera a ser utilizada é o nitrogênio, ele pode se difundir para o interior da peça, facilitando a formação de nitretos de alumínio (15)(16) . O nitreto de alumínio formado pelo calor liberado durante a reação do alumínio com o nitrogênio induz a uma fusão local, que por sua vez melhora a sinterização (15) .…”
Section: Introductionunclassified
“…Quando a atmosfera a ser utilizada é o nitrogênio, ele pode se difundir para o interior da peça, facilitando a formação de nitretos de alumínio (15)(16) . O nitreto de alumínio formado pelo calor liberado durante a reação do alumínio com o nitrogênio induz a uma fusão local, que por sua vez melhora a sinterização (15) . O que também pode ocorrer, é a sua formação no limite dos poros fechados, reduzindo a pressão no seu interior, podendo surgir dois efeitos na contração.…”
Section: Introductionunclassified